A chromosome-level genome of the booklouse, Liposcelis brunnea, provides insight into louse evolution and environmental stress adaptation. (19th July 2022) - Feng, Shiqian; Opit, George; Deng, Wenxin; Stejskal, Vaclav; Li, Zhihong
Abstract: Background: Booklice (psocids) in the genus Liposcelis (Psocoptera: Liposcelididae) are a group of important storage pests, found in libraries, grain storages, and food-processing facilities. Booklice are able to survive under heat treatment and typically possess high resistance to common fumigant insecticides, hence posing a threat to storage security worldwide. Results: We assembled the genome of the booklouse, L. brunnea, the first genome reported in Psocoptera, using PacBio long-read sequencing, Illumina sequencing, and chromatin conformation capture (Hi-C) methods. After assembly, polishing, haplotype purging, and Hi-C scaffolding, we obtained 9 linkage groups (174.1 Mb in total) ranging from 12.1 Mb to 27.6 Mb (N50: 19.7 Mb), with the BUSCO completeness at 98.9%. In total, 15, 543 genes were predicted by the Maker pipeline. Gene family analyses indicated the sensing-related gene families (OBP and OR) and the resistance-related gene families (ABC, EST, GST, UGT, and P450) expanded significantly in L. brunnea compared with those of their closest relatives (2 parasitic lice). Based on transcriptomic analysis, we found that the CYP4 subfamily from the P450 gene family functioned during phosphine fumigation; HSP genes, particularly those from the HSP70 subfamily, were upregulated significantly under high temperatures. Conclusions: We present a chromosome-level genome assembly of L. brunnea, the first genome reported for the order Psocoptera. Our analyses provide new insights into the gene family evolution of the louse clade and the transcriptomic responses of booklice to environmental stresses.